Design principles of Eurocode 2 - Nakov, Darko (Macedonian Association of Structural Engineers (MASE), 2022)
The adoption and implementation of new standards for design and execution of structures in one country is complex and long term process, which requires active participation of all available experts, institutes and organizations. If the same standards are expected to be implemented in more countries, than the process is even more complex, since there should be a lot of compromises, denials or adjustments with regards to the current design and execution praxis. The need for harmonization of technical standards within the European Community for the past few decades has led to the development of new technical standards in the field of civil engineering, so called Structural Eurocodes, or just Eurocodes. The use of these common standards is intended to lower trade barriers for construction products and enable companies and engineers to compete and work on a more equitable basis throughout Europe. Further, they are meant to lead to more uniform levels of safety in construction in Europe. The Eurocodes have been adopted, or there is an interest for adoption in many other countries in Europe and on other continents, as well. Еurocodes are set of 10 standards: EN 1990-Basis of structural design, EN 1991-Actions on structures, EN 1992, EN 1993, ЕN 1994, EN 1995, EN 1996, EN 1999-Design of concrete, steel, composite, timber, masonry and aluminum structures, accordingly, EN 1997-Geotechnical design and EN 1998-Design of structures for earthquake resistance. This paper refers primarily to the first part of Eurocode 2, named EN 1992-1-1: General rules and rules for buildings. Since Eurocodes are based on the limit states design, design principles and procedures for reinforced concrete members at the ultimate limit states will be explained and discussed (bending without and with axial loading, shear, torsion and punching).
Keywords: Eurocode 2, ultimate limit states, bending, shear, torsion, punching